Physical performance in elite male soccer under extreme heat: A case study of the 2025 FIFA Club World Cup - Carmo, A. A. L.; Souza-Junior, R. C. S.; Ferretti, P. H. S.; Gontijo, L. A.; Prado. L. S.; Teixeira, F.; Promola-Gomes, T. N.; Mündel, T.; Bitencourt, B. T.; Torres-Pinto, R. A.; Wanner, S. P. (Temperature, 2026)
The 2025 FIFA Club World Cup was held primarily during the summer season in the Northern Hemisphere, with reports of athletes exposed to significant environmental heat stress. We investigated whether environmental conditions, along with other factors (e.g., time of day, players` age and field position, and club geographic origin), influenced physical performance in this tournament. Information about the performance during 57 matches (n = 1070 observations) was extracted from FIFA technical reports, whereas environmental conditions were obtained through mathematical modeling (ERA5 reanalysis). Linear mixed models were used to identify factors that explained variance in total distance covered and in distances covered at high, moderate, and low speeds. Mean wet-bulb globe temperature (WBGT) exceeded 28°C in 31 of the 57 matches analyzed, confirming that players were exposed to conditions of extreme heat illness risk. WBGT and air temperature explained total distance and distances at different speeds, while relative humidity explained distance only at high speeds (p < 0.001). More specifically, high WBGT, air temperature, and relative humidity values reduced the distances covered. Other factors also influenced players` performance, including their position and age, time of day, and club geographic origin: longer distances were observed in midfielders/forwards, younger players, in the evening, and in clubs from cold climates (p < 0.05). In conclusion, the findings from this tournament, which featured many matches under extreme heat, highlight the multifaceted regulation of physical performance in soccer and emphasize the prominent role of environmental conditions in determining the distance players cover at different speeds.